The “Thal-index” with the BTT prediction.exe to discriminate Beta thalassaemia traits from other microcytic anaemias. - Nilanga Nishad (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
RBC parameters are used to differentiate beta thalassaemia traits (BTT) from other anaemias with different indices. The individual RBC parameters have shown a promise in differentiating BTT from other anaemias but we wanted a more precise way which suits our settings where the HPLC facilities are not available. We used the Fishers stepwise linear discriminant analysis.